Nutrient availability in tropical soils fertilized with sewage sludge and natural phosphate - Rodinei Facco Pegoraro; Jefferson Rodrigo Teixeira Silva; Leidivan Almeida Frazão; Regynaldo Arruda Sampaio; Silvana Ferreira Bicalho; Verônica Aparecida Santos Ferreira Soares (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The use of sewage sludge associated with natural rock-based fertilizers can increase nutrient solubility and soil fertility. From this perspective, this study evaluated changes in the chemical soil attributes and the nutrient availability rate after the application of sewage sludge, natural phosphate, and elemental sulfur in soils with different clay contents. Method: The study was conducted in a controlled environment and was set up in a completely randomized design with four replications in a 3 x 5 x 5 factorial arrangement consisting of soil with three clay contents: 28%, 34%, and 42%; five fertilization managements: unfertilized (Control), fertilized with natural phosphate (NF), fertilized with sewage sludge (SS), fertilized with natural phosphate and elemental sulfur (NF+S), and fertilized with NF+S+SS; and five evaluation times: 0, 30, 60, 90, and 120 days after fertilization. The chemical soil attributes and the nutrient availability rate were evaluated. Results: The application of sludge, natural phosphate, and sulfur increased the contents of SOM, N, P, K, Ca, Mg, Al, H+Al, SB, and CEC and reduced the soil pH, in addition to favoring the rate and time of availability of P, Ca, and Mg, with means higher than 50% in the soils from 30 to 120 days after application. At 120 days after application of sludge, the average availability rate of P, K, Ca, and Mg corresponded to 37, 13, 144, and 157%, respectively. Conclusion:These improvements imply savings with mineral fertilizers and contribute to adopting conservationist and sustainable practices. The individual application of sewage sludge or its application with natural phosphate and elemental sulfur increased soil fertility and the nutrient availability rate in soils with different clay contents. Highlights